S1P/S1PR1 signaling is involved in the development of nociceptive pain - Dong, Daosong; Yu, Xue; Tao, Xueshu; Wang, Qian; Zhao, Lin (Frontiers in Pharmacology, 2024)
Pain is a multidimensional perception that includes unpleasant somatosensory and emotional experiences; However, the underlying mechanisms that mediate the different components of pain remain elusive.Sphingosine phosphate 1 (S1P) is one of the metabolites of sphingomyelin and a highly bioactive lipid mediator. S1P initiates the classical G protein coupled receptor (GPCR) signaling pathway by binding to the cell surface homologous receptor (S1PRs), and can be used as the second messenger to participate in cell proliferation and apoptosis. Changes in S1P expression or abnormal S1PRs structure can lead to many diseases, such as multiple sclerosis, systemic lupus erythematosus, rheumatoid arthritis, ulcerative colitis and so on. However, the neuropharmacology of sphingolipid signal transduction in the central nervous system of pain conditions has been unexplored and controversial to a large extent. Our results confirmed that S1P/S1PR1 axis was involved in the cellular and molecular mechanism of nociceptive pain. S1P/S1PR1 signaling pathway regulated the activation of glial cells and the expression of painrelated genes STAT3, ERK, p38MAPK and inflammatory factors in spinal dorsal horn. Our results highlight the potential target of S1P system for the development of new analgesic drugs.